1994
DOI: 10.1002/ps.2780410413
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of human sweat volatiles: An example of pattern recognition in the analysis and interpretation of gas chromatograms

Abstract: The analysis of the volatile components of human body odour is described with a view to establishing how individual identity can be reflected in an odour profile. In order to get good chromatographic replication, a recirculating system was built to load the samples of axillary sweat head-space into Tenax concentrating traps. The loading temperature and humidity could be controlled and trace volatiles concentrated. The head-space samples were desorbed from the trap and analysed by GLC. The GC/FID was interfaced… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2006
2006
2007
2007

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 6 publications
0
14
0
Order By: Relevance
“…Cotton is the most widely reported type o f material used for human odor collection for both canines [86,92] and instruments [43]. Nevertheless, no mention o f the percent composition or sterilness of the fabrics are listed.…”
Section: Methods Fo R Human Scent Collectionmentioning
confidence: 99%
See 3 more Smart Citations
“…Cotton is the most widely reported type o f material used for human odor collection for both canines [86,92] and instruments [43]. Nevertheless, no mention o f the percent composition or sterilness of the fabrics are listed.…”
Section: Methods Fo R Human Scent Collectionmentioning
confidence: 99%
“…Research has been carried out to determine the applicability o f pattern recognition in the analysis and interpretation o f gas chromatograms produced from the analysis o f human sweat [43]. This study utilized a recirculating system to load the sweat head-space into This study demonstrated that human scent identity is determined by both qualitative and quantitative differences in sweat volatiles,yet no attempt was made to identify the compounds present.…”
Section: 41 Components O F Human Sweatmentioning
confidence: 99%
See 2 more Smart Citations
“…Twins lived apart in this study, which excluded the possibility that their body odour was similar due to shared environmental factors. As with humans, dogs can match odours of twins but not of genetically unrelated individuals (Sommerville, McCormick and Broom 1994).…”
Section: Introductionmentioning
confidence: 99%